2021
DOI: 10.3389/fonc.2021.656078
|View full text |Cite
|
Sign up to set email alerts
|

tRNA-Derived Fragment tRF-17-79MP9PP Attenuates Cell Invasion and Migration via THBS1/TGF-β1/Smad3 Axis in Breast Cancer

Abstract: tRNA derivatives have been identified as a new kind of potential biomarker for cancer. Previous studies have identified that there were 30 differentially expressed tRNAs derivatives in breast cancer tissue with the high-throughput sequencing technique. This study aimed to investigate the possible biological function and mechanism of tRNA derivatives in breast cancer cells. One such tRF, a 5’-tRF fragment of tRF-17-79MP9PP (tRF-17) was screened in this study, which is processed from the mature tRNA-Val-AAC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 46 publications
(61 reference statements)
0
33
0
Order By: Relevance
“…In other diseases, speci c tRF&tiRNA have also been gradually considered as reliable biomarkers (Chen et al, 2021). In breast cancer, Serum tRF-17-79MP9PP, as a biological marker for detecting breast cancer, has a sensitivity of up to 70% (Mo et al, 2021). These altogether supported the great potential of exosomal tRFs as biomarkers in the diagnosis of diseases.…”
Section: Discussionmentioning
confidence: 97%
“…In other diseases, speci c tRF&tiRNA have also been gradually considered as reliable biomarkers (Chen et al, 2021). In breast cancer, Serum tRF-17-79MP9PP, as a biological marker for detecting breast cancer, has a sensitivity of up to 70% (Mo et al, 2021). These altogether supported the great potential of exosomal tRFs as biomarkers in the diagnosis of diseases.…”
Section: Discussionmentioning
confidence: 97%
“…In other diseases, speci c tRF&tiRNA have also been gradually considered as reliable biomarkers [19] . In breast cancer, Serum tRF-17-79MP9PP, as a biological marker for detecting breast cancer, has a sensitivity of up to 70% [20] . These altogether supported the great potential of exosomal tRFs as biomarkers in the diagnosis of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The tRF/miR-1280 derived from tRNA Leu and pre-miRNA inhibits Notch signaling pathway by directly targeting Notch ligand JAG2 mRNA 3′ UTR, inhibiting the growth and metastasis of colorectal cancer cells [ 18 ]. tRF-17-79MP9PP targets THBS1 3′ UTR to attenuate breast cancer cell invasion and migration [ 45 ]. In this study, we confirmed that NDFIP2 is the direct target of Gly-tRF.…”
Section: Discussionmentioning
confidence: 99%